Václav Havel: niepolityczny polityk - Bankowicz, Marek (Wydawnictwo Nauka i Innowacje, 2014)
The article presents the political and intellectual silhouette of Václav Havel (1936–2011) – the last president of Czechoslovakia and the first one of the Czech Republic. Havel, the next to the Pole Lech Wałęsa, is the world renown symbol of the political turning point of 1989 that ended the world communist system. Before 1989, during the communist age, Havel was a dramatist, essayist and leader of Czechoslovak anticommunist and democratic dissident movement. He was strongly persecuted by the ruling communists, and while living under a permanent supervision of the security services and he was many times arrested. In 1989 Havel became a president of democratic Czechoslovakia and after dissolving of this state, in 1993, he was elected as a the first president of the new Czech Republic, holding the office by 10 following years. Havel was very untypical politician and president. He has played rather the role of an intellectual for whom politics is a matter of changing reality not by political decisions, but as a result of impact the on world by ideas and views. To follow Thomas Garrigue Masaryk example, the founder and first head of Czechoslovak state, clearly admired by Havel, he has tried to conduct of non-political politics. In this model politics becomes a practical applying of ethics and most important within it is not a power or state procedures and mechanisms, but men’s good and faithfulness to the truth. Václav Havel went down in the history as one of the greatest political figures of the second half of the last century.
Václav Havel: Non-political Politician
Keywords: politics; non-political politics; dramatist; communism; dissident movement; democratic opposition; president; presidency; Czechoslovakia; Czech Republic